PET Parameters are Useful in Predicting Endometrial Cancer Risk Classes and Prognosis - Budak, Adnan; Beyan, Emrah; Inan, Abdurrahman Hamdi; Kanmaz, Ahkam Göksel; Aldemir, Onur Suleyman; Oral, Aylin; Yazici, Bulent; Akgün, Ayşegül; Ozeren, Mehmet (Nuklearmedizin - NuclearMedicine, 2020)
Aim We investigate the role of preoperative PET parameters to determine risk classes and prognosis of endometrial cancer (EC).Methods We enrolled 81 patients with EC who underwent preoperative F-18 FDG PET/CT. PET parameters (SUVmax, SUVmean, MTV, TLG), grade, histology and size of the primary tumor, stage of the disease, the degree of myometrial invasion (MI), and the presence of lymphovascular invasion (LVI), cervical invasion (CI), distant metastasis (DM) and lymph node metastasis (LNM) were recorded. The relationship between PET parameters, clinicopathological risk factors and overall survival (OS) was evaluated.Results The present study included 81 patients with EC (mean age 60). Of the total sample, 21 patients were considered low risk (endometrioid histology, stage 1A, grade 1 or 2, tumor diameter < 4 cm, and LVI negative) and 60 were deemed high risk. All of the PET parameters were higher in the presence of a high-risk state, greater tumor size, deep MI, LVI and stage 1B-4B. MTV and TLG values were higher in the patients with non-endometrioid histology, CI, grade 3 and LNM. The optimum cut-off levels for differentiating between the high and low risk patients were: 11.1 for SUVmax (AUC = 0.757), 6 for SUVmean (AUC = 0.750), 6.6 for MTV(AUC = 0.838) and 56.2 for TLG(AUC = 0.835). MTV and TLG values were found as independent prognostic factors for OS, whereas SUVmax and SUVmean values were not predictive.Conclusions The PET parameters are useful in noninvasively differentiating between risk groups of EC. Furthermore, volumetric PET parameters can be predictive for OS of EC.
Keywords: endometrial cancer risk classes; FDG PET CT; SUVmax; MTV; TLG; prognosis